Cover Feature: Quasi‐Emulsion Confined Synthesis of Edge‐Rich Ultrathin MoS2 Nanosheets/Graphene Hybrid for Enhanced Hydrogen Evolution (Chem. Eur. J. 3/2018). Issue 3 (8th November 2017) - Yin, Xuying; Yan, Ya; Miao, Mao; Zhan, Ke; Li, Pingwei; Yang, Junhe; Zhao, Bin; Xia, Bao Yu
Abstract : An edge‐rich ultrathin MoS2 /RGO hybrid prepared by a confinement synthesis and used as an electrocatalyst for hydrogen evolution is depicted. The glycerol‐generated quasi‐emulsion system offers a steric‐hindrance effect to confine the growth of tiny MoS2 nanosheets on the graphene substrates. Owing to the highly exposed active sites and enhanced conductivity, the MoS2 /RGO hybrid delivers excellent activity and decent stability toward the hydrogen evolution reaction. More information can be found in the Communication by Y. Yan, B. Zhao, B. Y. Xia et al. onpage 556 .